2009
DOI: 10.1073/pnas.0810968106
|View full text |Cite
|
Sign up to set email alerts
|

The physiologic aggresome mediates cellular inactivation of iNOS

Abstract: Nitric Oxide (NO), produced by inducible nitric oxide synthase (iNOS), has been implicated in the pathogenesis of various biological and inflammatory disorders. Recent evidence suggests that aggresome formation is a physiologic stress response not limited to misfolded proteins. That stress response, termed ''physiologic aggresome,'' is exemplified by aggresome formation of iNOS, an important host defense protein. The functional significance of cellular formation of the iNOS aggresome is hitherto unknown. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…In the cytosol, responses to unfolded proteins include chaperon refolding, aggresome sequestration, and protein degradation (2,5,6). In contrast to UPR in the ER, the regulatory molecules operative in cytosolic responses and their potential relation to ER stress are not well elucidated.…”
mentioning
confidence: 99%
“…In the cytosol, responses to unfolded proteins include chaperon refolding, aggresome sequestration, and protein degradation (2,5,6). In contrast to UPR in the ER, the regulatory molecules operative in cytosolic responses and their potential relation to ER stress are not well elucidated.…”
mentioning
confidence: 99%
“…We previously showed that RPN13 physically interacts with NOS2, modulating its activity through blocking its homodimerization and potentially targeting nascent NOS2 polypeptides into a membrane-bound location (21)(22)(23). NOS2 inactivation is also likely to be achieved by targeting this enzyme into a proteasome-dependent degradation pathway, modulating NOS2 turnover and protecting cells against longterm and high-output NO production by this powerful enzyme (5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin Induces the Phospho-⌬Np63␣/RPN13-dependent Proteasome Degradation of NOS2-RPN13 was previously found to bind NOS2 and to inactivate its function through 1,3,5,7,9,11,13, and 15) and 10 g/ml cisplatin (CIS; ϩ; samples 2,4,6,8,10,12,14, and 16) for 16 h were transfected with the pGL3 constructs for the 1750-bp RPN13 promoter and 5Ј-deletions. Samples 1 and 2, control (empty vector); samples 3 and 4, Ϫ1750/ϩ50 bp; samples 5 and 6, Ϫ1280/ϩ50 bp; samples 7 and 8, Ϫ1192/ϩ50 bp; samples 9 and 10, Ϫ1043/ϩ50 bp; samples 11 and 12, Ϫ901/ϩ50 bp; samples 13 and 14, Ϫ608/ϩ50 bp; samples 15 and 16, Ϫ331/ϩ50 bp.…”
Section: Cisplatin-induced Phospho-⌬np63␣ Interacts With Other Transcmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the general importance of this residue, we further studied the sensitivity of iNOS mutants to BBS-2, a selective iNOS dimerization inhibitor (25,26). We observed that 2 M BBS-2 decreased NO production around 75% by wild-type iNOS or iNOS mutants E658A, E658K, and E658Q (supplementary Fig.…”
Section: Detailed Mutational Analysis Of E658 Residue Reveals Strikinmentioning
confidence: 99%